The Palu-Uluova Strike-Slip Basin in the East Anatolian Fault System, Turkey: Its Transition from the Palaeotectonic to Neotectonic Stage - Colak, Serap; Aksoy, Ercan; Kocyigit, Ali; Inceoz, Murat (Tubitak Scientific & Technological Research Council Turkey, 2012)
The East Anatolian fault system (EAFS) is the 80-km-wide, 700-km-long, NE-trending sinistral strike-slip fault system forming a seismically very active intracontinental transfom fault boundary. It is located between Karhova County in the northeast and Karatas-Samandag counties in the southwest, and forms the southeastern boundary of the Anatolian platelet. The Palu-Uluova basin is one of several strike-slip basins located along the EAFS. It is surrounded by several push-ups such as the Karaomerdagi, Mastardagi and Askerdagi push-ups caused by the complexities peculiar to strike-slip faulting. The Palu-Uluova basin consists of three sub-sections: two are NE-trending strike-slip sub-basins, the Uluova and the Palu-Kumyazi sub-basins, while the third is a ramp basin, the E-W-trending Yolustu basin which links the earlier two sub-basins. The Palu-Uluova basin is characterized and shaped by a 130-m-thick neotectonic basin infill (Palu Formation) and a series of bounding strike-slip fault zones such as the Sivrice, Adiyaman, Uluova, Elazig, Pertek and Yolustu fault zones. The Palu Formation is an undeformed fluvio-lacustrine sedimentary sequence. The youngest palaeotectonic rock-stratigraphic unit is the Upper Miocene-Lower Pliocene caybagi Formation, deposited in a ramp type of intermontane basin bounded and controlled by the reverse faults. The caybagi Formation is intensely deformed (steeply tilted, folded and thrust to reverse-faulted) on a regional (mappable) scale. The compressional deformation pattern of the Caybagi Formation is truncated, sealed and overlain with angular unconformity by the nearly horizontal undeformed Plio-Quaternary Palu Formation. This regional angular unconformity reflects: (a) a series of pre-Late Pliocene regional tectonic inversions (e.g., type of the tectonic regime, style of deformation and nature of magmatic activity), and (b) the timing of the major transition from the folding and thrust to reverse faulting-dominated palaeotectonic period into the strike-slip faulting-dominated neotectonic period is Late Pliocene.
Do?u Anadolu fay sistemi üzerindeki Palu-Uluova do?rultu atımlı fay havzası, Türkiye: Paleotektonik dönemden neotektonik döneme geçiş
Keywords: East Anatolian fault system; Palu-Uluova strike-slip basin; intermontane basin; Turkey